Analisis Kemampuan Komunikasi Matematis pada Materi Bentuk Aljabar Siswa Kelas VII SMPN 16 Mataram - Tina Septikayanti; Sudi Prayitno; Eka Kurniawan; Nani Kurniati (Griya Journal of Mathematics Education and Application, 2022)
This study aims to analyze and describe how written mathematical communication skills are when This study aims to analyze and describe how written mathematical communication skills when solving algebraic questions are based on the mathematics abilities of seventh grade students of SMP Negeri 16 Mataram in the academic year 2020/2021. This type of research is descriptive research with a qualitative approach. The populasi in this study was 154 class VII students of SMP Negeri 16 Mataram in the academic year 2020/2021 and the number of research samples was 32 students taken by purposive sampling technique. The subject selection technique is based on the results of the written mathematical communication ability test, 9 subjects will be analyzed from 32 students. Each category of mathematical communication ability has 3 students. There are 3 students in each category of mathematical communication skills. The aspects of written mathematical communication skills, namely writing text, drawing, and symbolic. Based on the results of data analysis obtained, it can be concluded, (i) The ability of mathematical communication in the aspect of writing texts, high-ability students are in good category, namely students can write down information that is known and asked, students can write down ideas when solving problems correctly. Meanwhile, students with moderate and low abilities are categorized as sufficient, that is, some of the students can write down the information that is known and asked completely. And students can write down ideas in solving problems. (ii) In the drawing aspect, students with high and moderate abilities are categorized as good, namely students can express problems in the form of pictures correctly and completely. Meanwhile, students who have low ability in the aspect of drawing are categorized as sufficient, that is, students can state mathematics problems in the form of pictures accompanied by descriptions. (iii) In the symbolic aspect, students who are capable of mathematics are categorized as sufficient, namely students can use mathematics symbols when writing information that is known and asked, students can write down ideas in solving problems and students can write descriptions of pictures using mathematics symbols.